The Influence of Integrated Marketing Communication and Brand Equity on Sales Volume of Pt. Medan Diesel Union - Putri Mauliza (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
The purpose of this study is to determine the effect of Personal Selling, Sales Promotion and Brand Equity on Sales Volume at PT. Uni Diesel. The population in this study are customers of PT. Uni Diesel totaling 4.907 customers. The technique of determining the samples used in this study is Slovin formula and totaling 98 respondents. The research method used is the technique of collecting data through library research conducted systematically based on research objectives. The analytical method used to solve problems and prove hypotheses with descriptive analysis, regression analysis. This analysis includes validity and reliability, classic assumption test, multiple regression analysis, hypothesis testing through t and F test, and test the coefficient of determination (R2). The t test results show Personal Selling variable had a positive and significant on Sales Volume at PT. Uni Diesel. Sales Promotion variable had a positive and significant on Sales Volume at PT. Uni Diesel. Brand Equity variable variable had a positive and significant on Sales Volume at PT. Uni Diesel. The F test results show that the independent variables Personal Selling, Sales Promotion and Brand Equity adjusted for the variable Sales Volume. Test results of the coefficient of determination (R2) indicate that Sales Volume variable are supported by Personal Selling, Sales Promotion and Brand Equity variables.